Hydroalcoholic extract of Buxus sempervirens shows antiproliferative effect on melanoma, colorectal carcinoma and prostate cancer cells by affecting the autophagic flow - Volpe, Anna Rita; Carmignani, Marco; Cesare, Patrizia (Frontiers in Pharmacology, 2023)
Buxus sempervirens (boxwood) has been used in folk medicine to treat rheumatism, arthritis, fever, malaria and skin ulceration while, in recent years, interest has grown on possible employment of boxwood extracts in cancer therapy. We studied the effect of hydroalcoholic extract from dried leaves of B. sempervirens (BSHE) on four human cell lines (BMel melanoma cells, HCT116 colorectal carcinoma cells, PC3 prostate cancer cells, and HS27 skin fibroblasts) to ascertain its possible antineoplastic activity. This extract inhibited proliferation of all cell lines in different degree as shown, after 48 h- exposure and MTS assay, by the values of GR50 (normalized growth rate inhibition50) that were 72, 48, 38 and 32 µg/mL for HS27, HCT116, PC3 and BMel cells, respectively. At the above GR50 concentrations, 99% of all studied cells remained vital showing accumulation of acidic vesicles in the cytoplasm, mainly around nuclei, whereas a higher extract concentration (125 µg/mL) was cytotoxic causing, after 48h-exposure, death of all BMel and HCT116 cells. Immunofluorescence showed microtubule-associated light chain 3 protein (LC3, a marker for autophagy) to be localized on the above acidic vesicles when cells were treated for 48h with BSHE (GR50 concentrations). Western blot analysis revealed, in all treated cells, a significant increase (2.2-3.3 times at 24h) of LC3II, i.e. the phosphatidylethanolamine conjugate of the cytoplasmic form LC3I that is recruited in autophagosome membranes during autophagy. Such increase was accompanied, in all cell lines treated for 24h or 48h with BSHE, by a significant increment (2.5-3.4 times at 24h) of p62, an autophagic cargo protein undergoing degradation during the autophagic process. Therefore, BSHE appeared to promote autophagic flow with its following blockade and consequent accumulation of autophagosome or autolysosomes. The antiproliferative effects of BSHE also involved cell cycle regulators such as p21 (HS27, BMel and HCT116 cells) and cyclin B1 (HCT116, BMel and PC3 cells) whereas, among apoptosis markers, BSHE only decreased (30-40% at 48h) the expression of the antiapoptotic protein survivin. It was concluded that BSHE impairs autophagic flow with arrest of proliferation and death in both fibroblasts and cancer cells, being the latter much more sensitive to these effects.